2018
DOI: 10.1063/1.5059561
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity of graphene grain boundaries along arbitrary in-plane directions: A comprehensive molecular dynamics study

Abstract: The thermal conductivity of polycrystalline graphene is expected to be lower than that of pristine graphene, due to the existence of defects, such as grain boundaries (GBs). To study the thermal transport behavior in polycrystalline graphene, it is crucial to understand the thermal conductivity of graphene GBs as a function of the tilt GB misorientation angle and in-plane thermal loading angle. However, existing studies of thermal conductivity of graphene GBs only consider the case where the thermal flux is pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…The reason for the emergence of the C peak was hydrogen annealing caused new chemical bonds between graphene layer and the FINEMET ribbon, such as Si-H and Si-H 2 bond. 14 There were three main effects for the FINEMET/ graphene composite ribbons during the hydrogen annealing process: [15][16][17][18][19] the rst was to remove contaminants (PMMA, etc. ), the second was to saturate the surface metal dangling bonds, and the third was to form hydrogen bonds and Si-H bonds to increase adhesion between the FINEMET ribbon and graphene.…”
Section: Resultsmentioning
confidence: 99%
“…The reason for the emergence of the C peak was hydrogen annealing caused new chemical bonds between graphene layer and the FINEMET ribbon, such as Si-H and Si-H 2 bond. 14 There were three main effects for the FINEMET/ graphene composite ribbons during the hydrogen annealing process: [15][16][17][18][19] the rst was to remove contaminants (PMMA, etc. ), the second was to saturate the surface metal dangling bonds, and the third was to form hydrogen bonds and Si-H bonds to increase adhesion between the FINEMET ribbon and graphene.…”
Section: Resultsmentioning
confidence: 99%
“…28 Besides, Fox et al investigated the effects of thermal loading direction and the grain boundary misorientation angle on the thermal conductivity of graphene with grain boundaries. 29 They found that the thermal conductivity generally decreases with increasing defect density along the grain boundaries, but increases with increasing the loading angle. Analogously, the formation of wrinkles could also decrease the thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…[ 13 ] In graphene, GBs are strings of pentagon‐heptagon (5‐7) edge dislocations [ 10 , 14 , 15 , 16 ] and their organization can gives rise to diverse GB shapes. While in general the thermal gradient can have an arbitrary orientation with respect to the GB line, [ 17 , 18 ] only transport across GBs is perceived to have a significantly impact on heat transport. Green's function (GF) calculations [ 19 , 20 ] obtained that heat transmission across GBs can be influenced by the GB structure, size, and shape.…”
Section: Introductionmentioning
confidence: 99%